SEXUAL SADISM AND MASOCHISM IN CHARACTER KEVIN MORANO IN NOVEL SEDUCTION IN DEATH BY J.D ROBB - Pelangi, Kinanti (LANTERN (Journal on English Language, Culture and Literature), 2017)
This final project is to analyze novel, Seduction in Death by J.D Robb. The purpose of this final project is to know sexual disorder owned by the character in the novel Seduction in Death. The sexual disorder is sadism and masochism. In analysis this novel, the writer uses a literary research method and Sigmund Freud’s psychoanalysis theory. The Result shows that there are sexual needs unfulfilled by Kevin Morano that ultimately he commits sadism and masochism.